The librarians of Lisbon [large type] - Nelson, Suzanne, 1976- (Thorndike Press large print basic, 2025)
"With World War II raging across Europe, best friends Selene Delmont and Beatrice Sullivan are enlisted by the US Intelligence Office and sent to Lisbon--a sparkling city and hotbed of trouble, harboring exiled royalty, hunted refugees, and spies trading double-edged secrets in seductively dark corners. In official capacity, librarians Selene and Bea have been recruited to catalog the vast mountain of information gathered by the Allies, but by night, both women are undercover agents tasked with infiltrating the Axis spy network. Where Selene is confident and brash, Bea is bookish and careful. Selene longs to escape her family's impossible expectations and embrace her independence, while all Bea wants is to heal from heartbreak and keep impulsive Selene out of trouble. But soon, both librarians are caught up in treacherous games of deception alongside two of Lisbon's most notorious men--the outcast Portuguese baron, Luca Caldeira, and the lethal double agent, Gable. As Selene charms her way through lavish ballrooms and fêtes with Luca, Bea is plunged into Gable's shadowy underworld of informants. Victory depends upon the joint success of their missions, but when an unexpected betrayal throws a carefully spun web of lies into chaos, everything they've sacrificed is put at risk. As Selene and Bea are pushed to their breaking points, can their friendship, and their hearts, survive the cost of war?"--